Interleukins in diagnosis of perinatal asphyxia: A systematic review - Hassan Boskabadi; Ali Moradi; Maryam Zakerihamidi (Shahid Sadoughi University of Medical Sciences, 2019)
Abstract Background Biochemical markers including interleukins (ILs) has been proposed for early diagnosis of asphyxia Objective This study has aimed to systematically review the significance of IL measurements in the diagnosis of perinatal asphyxia. Materials and Methods PubMed, Cochrane Library, Web of Science, Embase, and Scopus databases before 2017 were searched for the following keywords: asphyxia, neonatal, interleukin, and diagnosis. A total of 13 out of 300 searched papers were finally selected for evaluation. Interleukins under study were IL6 and interleukin 1 β (IL-1 β ). Interleukins had been measured in 10 studies by serum samples, 2 studies by samples of Cerebro Spinal Fluid (CSF), and 1 study by sample of umbilical cord blood. The inclusion criteria were: studies on neonates, with adequate information from the test results and studies using markers other than ILs to detect asphyxia; however, studies with only abstracts available were excluded. Results Research on the issue suggests that IL6 > 41 Pg/dl has the sensitivity of 84.88% and the specificity of 85.43%, whereas IL-1 β > 4.7 Pg/dl has the sensitivity of 78% and specificity of 83% in the diagnosis of neonatal asphyxia. Among diagnostic ILs for neonatal asphyxia, combination of IL6 and IL-1 β had the highest sensitivity, that is, 92.9%. Conclusion IL6 and IL-1 β of serum samples were used in the early diagnosis of perinatal asphyxia and are useful predictors for the outcomes of perinatal asphyxia and its intensity. In addition, simultaneous evaluation of IL-1 β and IL6 can improve the sensitivity of the early diagnosis of perinatal asphyxia.